Phenotypic Stability of Yield and its Components in Pearl Millet - Yadav, Gaurav; Yadav, H P; Yadav, Y P (Annals of Arid Zone, 2016)
The stability of twenty four genotypes of pearl millet were evaluated for their stability by growing them in four different environments. Partitioning of mean sum of squares according to environments suggested that Â·performance of genotypes across the environment could be predicted for grain yield, ear length and ear weight, whereas for 1000-grain weight and 50% flowering, both linear and non-linear components were equally important. The magnitude of linear and non-linear components of G x E interaction revealed that linear portion was more for ear length (85.86%), ear weight (78.94%) and grain yield (70%). Only hybrid HHB 118 did well under all conditions. HHB 94, HHB 128 and HP 91773 are good for favorable environments, and HHB 68, HP9 12 and HP 9550 I could be recommended for poor environments.